Pre-Sowing Seed Treatment with Gamma Rays, Ethyl Methanesulphonate and Sodium Azide in Lentil (Lens culinaris) Cultivar Shekhar-4 - KIRAN KUMARI; PRASHANT KUMAR RAI; VAIDURYA PRATAP SAHI (Seed Research, 2025)
This study tested the effects of pre-sowing treatments—gamma rays, EMS, and SA—on lentil growth and yield. Lentil seeds (cv. Shekhar-4), stored for one season, were treated with various doses and grown under field and lab conditions. Seeds treated with 5 kR gamma rays showed the best growth and yield. Lower doses improved performance, while higher doses reduced it. Overall, gamma irradiation was most effective at lower levels.